Beta-Sitosterol Enhances Classical Swine Fever Virus Infection: Insights from RNA-Seq Analysis - Yayun Liu; Dongdong Yin; Jieru Wang; Yin Dai; Xuehuai Shen; Lei Yin; Bin Zhou; Xiaocheng Pan (Viruses)
Beta-sitosterol (BS), a naturally occurring phytosterol abundant in plants, has been reported to exhibit diverse biological activities, including immunomodulatory and antiviral effects. Classical swine fever virus (CSFV), a member of the Pestivirus genus, remains a persistent threat to the swine industry worldwide, causing considerable economic damage. Our research found that BS significantly enhances the replication of both the CSFV-Shimen strain and the attenuated C-strain vaccine virus in PK-15 cells. Additionally, transcriptomic profiling (RNA-Seq) identified 175 differentially expressed genes (DEGs) following BS exposure, comprising 53 upregulated and 122 downregulated genes. Further results demonstrated that treatment with β-sitosterol suppressed IκBα expression, thereby activating the NF-κB pathway, and that knockdown of endogenous IκBα significantly promoted CSFV replication. These findings contribute to a deeper understanding of how BS influences the CSFV infection process, suggesting its role as a host lipid-associated factor facilitating viral propagation.